INFLUENCE OF COMPETENCE AND COMMITMENT TO WORK ACHIEVEMENT OF EMPLOYEES IN PT. UNITED ROPE MEDAN - Muhammad Rizky Syahputra Tarigan; Robby Samuel Butar-butar; Hendra Hasibuan; Jonny Maruli Tua Siboro (Asian Journal of Innovation and Entrepreneurship, 2019)
ABSTACT                Work performance is the result of one's efforts determined by the ability of his personal characteristics and achievements on his role in the job. Factors that influence work performance are competence and commitment. Competence Competence is a basic characteristic, part of the personality inherent in a person, and its behavior can be predicted in various circumstances of work tasks. Commitment explains the differences in relations between members of the organiasu and other ethnicities (one of them is the organization itself). PT. United Rope Medan is a company engaged in rope production. The research method uses a quantitative approach, the type of research used is quantitative descriptive. Data collection is done by interviews, questionnaires and documentation studies. Analysis of the data used is multiple linear regression. The population is all employees totaling 478 people. Determination of samples in the study using the Slovin formula, so that a sample of 218 respondents was obtained. The results showed that competency and commitment simultaneously and partially had a positive and significant effect on employee performance with a determinant coefficient of 0.857 or 85.7%, while the remaining 14.3% was influenced by other factors. The conclusion of the study is that simultaneously and partially competence and commitment have a significant effect on the achievement at PT. United Rope Medan.